Youth in times of polycrises: the role of social support in connection with the depression and anxiety symptoms among young people in polish secondary schools during the COVID-19 threat and the outbreak of war in Ukraine - Badura-Brzoza, Karina; Główczyński, Patryk; Tatar, Dominika; Dębski, Paweł (Frontiers in Psychology, 2025)
AimTo assess perceived social support and its relationship with symptoms of depression and anxiety among secondary school students in a crisis situation such was the outbreak of the Russian-Ukrainian war and the ongoing Covid 19 pandemic.Materials and methodsThe study involved 1,456 students aged 14–19 (mean age 16.77 ± 1.33), including 776 girls and 680 boys. Data were collected during a single data collection period from February 2022 to May 2022. Participants completed the Multidimensional Scale of Perceived Social Support (MSPSS), Children’s Depression Inventory 2 (CDI-2), the State–Trait Anxiety Inventory (STAI-X1), and a sociodemographic questionnaire. Data were analyzed using non-parametric tests and correlation analyses.ResultsGirls reported significantly higher levels of perceived social support from significant people and friends as well as higher symptoms of depression and anxiety, compared to boys. Negative correlations were found between perceived social support and symptoms of depression and anxiety in both genders.ConclusionThe conducted research indicates that perceived social support may play an important role in coping with symptoms of anxiety and depression in crisis situations.